# RD Sharma Class 12 Ex 22.4 Solutions Chapter 22 Differential Equations

Here we provide RD Sharma Class 12 Ex 22.4 Solutions Chapter 22 Differential Equations for English medium students, Which will very helpful for every student in their exams. Students can download the latest RD Sharma Class 12 Ex 22.4 Solutions Chapter 22 Differential Equations book pdf download. Now you will get step-by-step solutions to each question.

## RD Sharma Class 12 Ex 22.4 Solutions Chapter 22 Differential Equations

### Function: y = logx

Solution:

We have,

y = logx          -(1)

On differentiating eq(1) w.r.t x,

dy/dx = (1/x)

x(dy/dx) = 1

Thus, y = logx satisfy the given differential equation.

If x = 1, y = log(1) = 0

So, y(1) = 0

### Function: y = ex

Solution:

We have,

y = ex          -(1)

On differentiating eq(1) w.r.t x

dy/dx = ex

(dy/dx) = y

Thus, y = ex satisfy the given differential equation.

If x = 0, y = e= 1

So, y(0) = 1

### Function: y = sinx

Solution:

We have,

y = sinx           -(1)

On differentiating eq(1) w.r.t x,

(dy/dx) = cosx          -(2)

Again, differentiating eq(2) w.r.t x,

d2y/dx= -sinx

d2y/dx+ sinx = 0

Thus, y = sinx satisfy the given differential equation.

If x = 0, y(0) = sin(0) = 0

y'(0) = cos(0) = 1

### Function: y = ex + 1

Solution:

We have,

y = e+ 1           -(1)

On differentiating eq(1) w.r.t x,

(dy/dx) = ex           -(2)

Again differentiating eq(2) w.r.t x,

d2y/dx= ex

d2y/dx– e= 0

d2y/dx– (dy/dx) = 0

Thus, y = e+ 1 satisfy the given differential equation.

If x = 0, y(0) = e+ 1, y(0) = 1 + 1 = 2

y'(0) = e= 1

### Function: y = e-x + 2

Solution:

We have,

y = e-x + 2           -(1)

On differentiating eq(i) w.r.t x,

(dy/dx) = -e-x

(dy/dx) + e-x = 0

(dy/dx) + (y – 2) = 0

(dy/dx) + y = 2

Thus, y = e-x + 2 satisfy the given differential equation.

If x = 0, y(0) = e-0 + 2 = 1 + 2 = 3

### Function: y = sinx + cosx

Solution:

We have,

y = sinx + cosx           -(1)

On differentiating eq(i) w.r.t x,

dy/dx = cosx – sinx           -(2)

Again differentiating eq(ii) w.r.t x,

d2y/dx= -sinx – cosx

d2y/dx= -(sinx + cosx)

(d2y/dx2) + y = 0

Thus, y = sinx + cosx satisfy the given differential equation.

If x = 0, y(0) = sin0 + cos0 = 1

y'(0) = cos0 – sin0 = 1

### Function: y = ex + e-x

Solution:

We have,

y = e+ e-x           -(1)

On differentiating eq(i) w.r.t x,

dy/dx = e– e-x           -(2)

Again differentiating eq(2) w.r.t x,

d2y/dx= e+ e-x

d2y/dx= y

d2y/dx– y = 0

Thus, y = e+ e-x satisfy the given differential equation.

If x = 0, y(0) = e+ e-0 = 1 + 1 = 2

y'(0) = e– e-0 = 0

### Function: y = ex + e2x

Solution:

We have,

y = e+ e2x           -(1)

On differentiating eq(1) w.r.t x,

dy/dx = e+ 2e2x           -(2)

Again differentiating equation(2) w.r.t x,

d2y/dx= e+ 4e2x

d2y/dx= 3(e+ 2e2x) – 2(ex + e2x)

(d2y/dx2) = 3(dy/dx) – 2y

(d2y/dx2) – 3(dy/dx) + 2y = 0

Thus, y = e+ e2x satisfy the given differential equation.

If x = 0, y(0) = e+ e= 1 + 1 = 2

y'(0) = e+ 2e= 1 + 2 = 3

### Function: y = xex + ex

Solution:

We have,

y = xe+ ex            -(1)

On differentiating eq(1) w.r.t x,

dy/dx = xe+ e+ e

dy/dx = xe+ 2ex           -(2)

Again differentiating eq(2) w.r.t x,

d2y/dx= xe+ e+ 2e

d2y/dx= xe+ e+ 2e+ xe+ e– xe– ex

d2y/dx= 2(xe+ ex) – (xe+ ex)

(d2y/dx2) = 2(dy/dx) – y

(d2y/dx2) – 2(dy/dx) + y = 0

Thus, y = xe+ ex satisfy the given differential equation.

If x = 0, y(0) = 0e+ e= 1

y'(0) = 0e+ 2e= 2

I think you got complete solutions for this chapter. If You have any queries regarding this chapter, please comment in the below section our subject teacher will answer you. We tried our best to give complete solutions so you got good marks in your exam.

If these solutions have helped you, you can also share rdsharmasolutions.in to your friends.